Hot Pressing of Electrospun PVdF-CTFE Membranes as Separators for Lithium Batteries: a Delicate Balance Between Mechanical Properties and Retention - Trequattrini,Francesco (2018)
A systematic investigation of the effect of hot-pressing on polyvinylidene fluoride (PVdF) - chlorotrifluoroethylene (CTFE) electrospun membranes, intended as separators and substrate for the electrolyte of lithium batteries, has been carried out by means of dynamic mechanical analysis. Absorption and desorption gravimetric measurements and infrared spectroscopy have been also performed. In particular, the mechanical properties of the membranes have been measured as a function of hot pressing temperature and pressure in the range 20 - 120 °C and 0 - 4 kbar, finding an increase of about 30 times of the tensile modulus after pressing at the highest temperature and pressure. Moreover, the conductivity of hot pressed membranes swelled by an ionic liquid measured as a function of temperature between - 60 and + 70 °C practically superimposes on that of the unpressed membrane.